2008
DOI: 10.5057/kei.7.163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bathing on Trapezius Muscle Fatigue Induced by Typewriting Task

Abstract: The effect of bathing on recovery of muscle fatigue in the trapezius was examined in 6 healthy male adults. The subjects performed four sets of 25-min typewriting tasks and then rested on a chair for one hour. The development and recovery of muscle fatigue in the upper trapezius was periodically monitored with an electromyogram (EMG) in parallel with subjective muscle fatigue, surface and core temperatures, and near-infrared spectroscopy tests. The surface EMG was recorded during a 15-sec contraction at 30% ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…From a methodological point of view, EMGs have often been used to investigate muscle fatigue [for example, [14][15][16][17][18] or expression of laughter [19,20]. However, there are few reports on studies that have employed EMG recording from a driver during acceleration in a real driving setting.…”
Section: Discussionmentioning
confidence: 99%
“…From a methodological point of view, EMGs have often been used to investigate muscle fatigue [for example, [14][15][16][17][18] or expression of laughter [19,20]. However, there are few reports on studies that have employed EMG recording from a driver during acceleration in a real driving setting.…”
Section: Discussionmentioning
confidence: 99%
“…If the head is located relatively forward compared to the trunk, it changes the head, neck and physical alignment, causing pain in the head, neck and spine, while also negatively affecting the balanced growth of the body 14 , 15 ) . This change in physical alignment in the sitting posture is a risk factor affecting body and trunk alignment.…”
Section: Introductionmentioning
confidence: 99%
“…These therapies have also been experientially used to alleviate the tension and fatigue of muscles in European countries and Japan 9,10) . A previous study revealed hot water bathing has a psychological rather than physiological effect on the recovery of muscle fatigue after repetitive VDT work for 1 hour 11) . Moreover, previous papers indicated carbonated spring water has a suppressive effect on the sympathetic nerve system 12) and elevates body temperature via an increase in dermal blood flow [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%